Immune Cell Plasticity Allows for Resetting of Phenotype From Effector to Regulator With Combined Inhibition of Notch/eIF5A Pathways - Imam, Shahnawaz; Dar, Pervaiz; Aziz, Saba Wasim; Zahid, Zeeshan A.; Sarwar, Haider; Karim, Tamanna; Faisal, Sarah; Haseeb, Ibrahim; Naqvi, Ahmed S.; Shah, Rayyan; Haque, Amna; Salim, Nancy; et al. (Frontiers in Cell and Developmental Biology, 2021)
Type 1 diabetes (T1D) results from the destruction of pancreatic β-cells caused by an altered immune balance in the pancreatic microenvironment. In humans as well as in mouse models, T cells are well recognized as key orchestrators of T1D, which is characterized by T helper (Th) 1 and Th17 cell bias and/or low/defective T-regulatory cells (Treg), and culminates in cytotoxic T-cell (CTL)-mediated destruction of β-cells. Refitting of immune cells toward the non-inflammatory phenotype in the pancreas may represent a way to prevent/treat T1D. Recently we developed a unique spontaneous humanized mouse model of type 1 diabetes, wherein mouse MHC-II molecules were replaced by human DQ8, and β-cells were made to express human glutamic acid decarboxylase (GAD) 65 auto-antigen. The mice spontaneously developed T1D resembling the human disease. Humanized T1D mice showed hyperglycemic (250–300 mg/dl) symptoms by the 4th week of life. The diabetogenic T cells (CD4, CD8) present in our model are GAD65 antigen-specific in nature. Intermolecular antigen spreading recorded during 3rd–6th week of age is like that observed in the human preclinical period of T1D. In this paper, we tested our hypothesis in our spontaneous humanized T1D mouse model. We targeted two cell-signaling pathways and their inhibitions: eIF5A pathway inhibition influences T helper cell dynamics toward the non-inflammatory phenotype and Notch signaling inhibition enrich Tregs and targets auto-reactive CTLs, rescues the pancreatic islet structure, and increases the functionality of β-cells in terms of insulin production. We report that inhibition of (eIF5A + Notch) signaling mediates suppression of diabetogenic T cells by inducing plasticity in CD4 + T cells co-expressing IL-17 and IFNγ (IL-17 + IFNγ +) toward the Treg cells phenotype.